THE FORM AND METHODS OF USING THE MUSICAL HERITAGE OF T. JALILOV AND Y. RAJABI - Yo‘ldoshali Botirov (Лучшие интеллектуальные исследования, 2024)
Abstract: This article describes the forms and methods of using the musical heritage of T. Jalilov and Yu. Rajabi, and scientifically analyzes the principles and methods present in the pedagogical heritage of these composers.